قاعدة التقرير والتغيير وأثرها على عوائد العرب في ضوء التطبيق المقاصدي: حديث (أم زرع) أنموذجا (Journal of Academic Research, 2018)
In the light of the scientific consolidation of legislation and research ways in (Islam-sharia) objectives and related them to (Hadith Mohammedan) which contained the branches of behaviors judgments and clarified its facohties with reports verifiers and the change between bringing good and keeping off  vices. So mustdepending  on directing the arabic revenues through the honorable profitic message and correcting it with nobility of character end best customs. Also changing what was ruined then purification of souls from what stained them of sins (evils) and illusion